Penggunaan Video untuk Meningkatkan Aktivitas dan Hasil Belajar Bercerita pada Siswa Kelas B Taman Kanak-Kanak An-Nahl Bandar Lampung - Suryandari, Wahyuning (STKIP PGRI Bandar Lampung, 2022)
This study aims to improve activities and learning outcomes of storytelling using video props in Class B students of An-Nahl Kindergarten Bandar Lampung in the 2019/2020 academic year. The method used in this research is the Classroom Action Research method or classroom action research which is carried out in 3 cycles, consisting of planning, implementation, observation and reflection. The research was carried out from August to September 2019 with a total of 18 students. The results of the research and observations obtained in the first cycle which scored 62 as many as 12 people, or 67%, with an average of 54 in the Enough category. In the second cycle, 15 students scored 62 or 83% with an average of 70 in the Good category. Meanwhile, in the third cycle, 18 students scored 62 or 100% with an average of 80 in the very good category. Observations of learning activities showed that the first cycle of students was 54% active, the second cycle was 70% active, and the third cycle was 80% active. Thus, the use of video can improve activities and learning outcomes for storytelling in Class B students of An-Nahl Kindergarten Bandar Lampung for the 2019/2020 academic year.